Bredemeyera divaricata, a new combination for the well-known Amazonian species of Polygalaceae - Pastore, José Floriano Barêa (Phytotaxa, 2014)
A recent effort to study Ferreira’s material brought to Paris from Lisbon in the beginning of the XIXth century revealed the identity of one often overlooked name in Polygalaceae, Badiera divaricata which had not been revised since its original publication. We provide the typification of the names involved and propose a new combination for the species nowadays known as Bredemeyera altissima.